A Foucauldian reading of mothers' views on the paternalism/autonomy debate in relation to the sexual practices of their intellectually disabled adult sons and daughters. Issue 2 (1st November 2014) - Foley, Simon
Abstract: The obstacles preventing intellectually disabled adults living in Ireland from enjoying a more optimal quality of life take multiple forms. This article focuses on the issues of sexual relations and autonomy in relation to a specific population subsumed under the intellectual disability umbrella term; namely adults with Down syndrome living in the parental home. The obstacle under examination is the contention that the paternalistic regime of care that many parents of adults with Down syndrome deploy is a principal factor in explaining why many of their sons and daughters have failed to find the boyfriends/girlfriends they seek. To explore this conjecture a series of semi-structured interviews were carried out with ten mothers of adults with Down syndrome. The main findings are that while all of the respondents acknowledged that they subjected their sons and daughters to a paternalistic regime of care, they denied any causal connection between this form of surveillance and the fact that, with one exception, none of their mainly thirty-something charges have yet embarked on a sexual relationship. To offer a sociological interpretation as to why this data takes the form it does, the Foucauldian framework is employed to theorise the accounts proffered by the respondents.